Hip Hop e feminismo negro nos processos de participação de jovens negras - Cássia Reis Donato (2012)
This work was devoted to understanding ways in which Black Feminism could be experienced by young black women beyond spaces, formats and meanings consolidated in the trajectories of other generations of the Black Women's Movement. The research was carried out with the women's organization Negras Ativas, a collective from the Metropolitan Region of Belo Horizonte linked to both Hip Hop and the Black Women's Movement. As methodological procedures we used participant observation, analysis of documents and materials of symbolic production, individual interviews and discussion groups, with the purpose of favoring interlocution, interpretation and argumentative practice between the different knowledge that are part of the investigative process. We analyzed dynamics of the social field in which the women's organization Negras Ativas inserts itself by using Hip Hop both as a strategy and as a space for collective action. By identifying opportunities and difficulties to political participation in this scenario, we investigated under what circumstances the Hip Hop may appear as something that escapes norms, regulations and frameworks that impact the collective action of young black women. We discussed whether and how the Hip Hop Culture, as an expression of these young black women, has been related to conflicts established in the public sphere that question certain social order and evidence black feminists flags and projects.